High-risk human papillomavirus testing in women with ASCUS cytology: results from The ATHENA HPV study - M.H. Stoler; T.C. Wright, Jr; A. Sharma (Publishing House TRILIST, 2021)
This study evaluated the clinical performance of the cobas 4800 HPV Test (Roche Molecular Systems, Pleasanton, CA, USA) for high-risk human papillomavirus (HR-HPV) testing with individual HPV-16/HPV-18 genotyping in women 21 years or older with atypical squamous cells of undetermined significance (ASCUS). Women (N = 47,208) were recruited in the United States during routine screening, and liquid-based cytology and HPV testing were performed. The ASCUS prevalence was 4.1% (1,923/47,208), and 1,578 women underwent colposcopy with valid results. The cobas 4800 HPV Test demonstrated performance comparable to the Hybrid Capture 2 test (QIAGEN, Gaithersburg, MD, USA) for the detection of cervical intraepithelial neoplasia (CIN) grade 2 or worse and grade 3 or worse. HPV-16/HPV-18+ women had a greater absolute risk of CIN 2 or worse compared with pooled HR-HPV+ and HR-HPV- women (24.4%, 14.0%, and 0.8%, respectively). The cobas 4800 HPV Test is clinically validated for ASCUS triage. HPV-16/HPV-18 genotyping can identify women at highest risk for high-grade cervical disease, and this additional risk stratification may be used in formulating patient management decisions.